Friendship networks and political opinions: A natural experiment among future French politicians - Yann Algan; Nicolò Dalvit; Quoc-Anh Do; Alexis Le Chapelain; Yves Zenou (Research Institute of Industrial Economics (IFN), 2019)
We study how friendship shapes students' political opinions in a natural experiment. We use the indicator whether two students were exogenously assigned to a short-term "integration group", unrelated to scholar activities and dissolved before the school year, as instrumental variable for their friendship, to estimate the effect of friendship on pairwise political opinion outcomes in dyadic regressions. After six months, friendship causes a reduction of differences in opinions by one quarter of the mean difference. It likely works through a homophily-enforced mechanism, by which friendship causes politically-similar students to join political associations together, which reinforces their political similarity. The effect is strong among initially similar pairs, but absent in dissimilar pairs. Friendship affects opinion gaps by reducing divergence, therefore polarization and extremism, without forcing individuals' views to converge. Network characteristics also matter to the friendship effect.
Keywords: C93; D72; Z13; 330; Political opinion; Polarization; Friendship effect; Social networks; Homophily; Extremism; Learning; Natural experiment